Pengaruh Digital Marketing, Pengalaman Pelanggan, Dan Kepercayaan Pelanggan Terhadap Minat Beli pada Platform Marketplace Facebook - Nashrul Ulum; Ika Listyawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of digital marketing, customer experience, and customer trust on purchase intention on the Facebook Marketplace platform. The background of this research lies in the increasing trend of online shopping via social media and the need to understand psychological and marketing factors that drive consumer purchase decisions. This research is expected to contribute theoretically to the literature on digital marketing and provide practical insights for business practitioners, particularly MSMEs, in optimizing their digital marketing strategies.The research method used is a quantitative approach with survey techniques by distributing questionnaires to 100 active Facebook Marketplace users in Semarang City. The research instrument was tested using validity and reliability tests, and data analysis was conducted through multiple linear regression to measure the influence of each independent variable on the dependent variable. The sampling technique used purposive sampling based on specific criteria relevant to the study objectives.The results indicate that digital marketing, customer experience, and customer trust have a positive and significant influence on purchase intention, both partially and simultaneously. These findings prove that effective digital marketing strategies, positive customer experiences, and strong trust levels can significantly enhance consumers' intention to purchase through the Facebook Marketplace platform. The study offers practical recommendations for businesses to improve sales conversions in the digital era.